America's working women: A documentary history, 1600 to the present - Baxandall, (1939- ...)., Rosalyn Fraad; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Accessible en ligne : https://archive.org/details/isbn_9780393312621
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

Les relations amoureuses entre les femmes du XVIe au XXe siècle. Essai historique. - Bonnet, Marie-Joe (Odile Jacob, 1995)
Voici la première histoire de l'amour entre les femmes qui, sur cinq siècles, de la Renaissance à nos jours, tienne compte à la fois du regard extérieur des hommes et de l'approche des lesbiennes elles-mêmes. Pour la première fois, aussi, une analyse à long terme est proposée qui dégage une évolution des moeurs, des mentalités et de la place des femmes dans la société. Jusqu'à présent, en effet, l'histoire des femmes occultait l'amour entre femmes, alors que les lesbiennes ont joué un rôle prépondérant dans les mouvements progressistes politiques et artistiques. Unique en son genre par son érudition, son approche pluridisciplinaire, ses mises en perspective originales et la période considérée, cet essai s'impose déjà comme un ouvrage de référence.
Première publication: 1981
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; droits des femmes*; europe; fem1000; fem7000; france; histoire; histoire des femmes*; histoire et politique; hétérosexisme; identités; identités LGBTQIA2+; invisibilités; lesbianisme; lit3220; premier cycle; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques